2021
DOI: 10.3390/agronomy11061089
|View full text |Cite
|
Sign up to set email alerts
|

Arundo donax L.: How High Photosynthetic Capacity Is Maintained under Water Scarcity Conditions

Abstract: Arundo donax L. (giant reed) is a perennial rhizomatous grass and has been identified as an important non-food biomass crop with capacity for cultivation in marginal and degraded lands where water scarcity conditions frequently occur due to climate change. This review analyzes the effect of water stress on photosynthetic capacity and biomass production in multiple giant reed ecotypes grown in different regions around the world. Furthermore, this review will attempt to explain the reason for the high photosynth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
2
4
0
Order By: Relevance
“…Although A. donax is a C3 photosynthetic metabolism species, it showed the highest Net CO 2 assimilation rate, stomatal conductance, RWC, leaf greenness, height and biomass, even higher than those of C4 P. virgatum and Miscanthus species. The higher Asat and g s values from A. donax agree with previous studies of Rossa et al [12], Sánchez et al [13], Ceotto et al [14], Papazouglou et al [45] and Nackley et al [46]. Under NW conditions, the CO 2 assimilation rates decreased, mainly due to the decrease in g s , but not because of the decrease in photosynthetic electron transport rate as reported in P. virgatum and A. donax by Sánchez et al [24].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although A. donax is a C3 photosynthetic metabolism species, it showed the highest Net CO 2 assimilation rate, stomatal conductance, RWC, leaf greenness, height and biomass, even higher than those of C4 P. virgatum and Miscanthus species. The higher Asat and g s values from A. donax agree with previous studies of Rossa et al [12], Sánchez et al [13], Ceotto et al [14], Papazouglou et al [45] and Nackley et al [46]. Under NW conditions, the CO 2 assimilation rates decreased, mainly due to the decrease in g s , but not because of the decrease in photosynthetic electron transport rate as reported in P. virgatum and A. donax by Sánchez et al [24].…”
Section: Discussionsupporting
confidence: 91%
“…A. donax has a C3 photosynthetic metabolism unlike the two previous species, but having as high photosynthetic rates as many C4 species [11]. This species is native to Asia and has been successfully established in the Mediterranean region and subtropical wetlands [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…My hypothesis that the riparian plant community composition and diversity would vary significantly among vegetation types and environmental settings was supported by the results. The GCBA vegetation type dominated by giant cane exhibited the lowest biodiversity and species richness of the three vegetation types, which is in line with the species' dense monotypic growing patterns that force native taxa out of river valleys and lowlands (Bell 1997, Coffman 2007b, a, Li 2012, Sánchez et al 2021. The other three vegetation types showed significantly higher biodiversity and species richness, which suggests that other nonnative species like tamarisk, common reed, and Bermuda grass, which are all indicator species of their respective vegetation types, are not dominating and overwhelming their environments so that other native taxa cannot coexist in the same habitat.…”
Section: How Vegetation Types Varied Over Environmental Gradientssupporting
confidence: 56%
“…The quantum yield results separated cultivars better than NaR at 4 weeks after the deficit irrigation indicating that photon use efficiency at this point was affected more by water stress than by N availability. Previous research showed that photon use efficiency coupled with water use efficiency in C 3 grasses that have high water demand (Sanchez et al, 2021) but not in C 4 grasses (Ghannoum et al, 2003;Soares-Cordeiro et al, 2009). Therefore, further work on C 3 grass such as Kentucky bluegrass to differentiate water use efficiency and NUE may provide more information on drought tolerant mechanisms.…”
Section: Effective Quantum Yieldmentioning
confidence: 99%